Turkish pastramı; the development of its modern processing technique and its preservation with vacuum packaging - Nazif Anıl (Eurasian Journal of Veterinary Sciences)
This research was carried out to develop a modern production technique for Turkish pastrami by using a drying chamber in which the climatic conditions could be controlled and to determine the storage conditions of the product for extended shelf life by vacuum packaging. Three different types of experimental pastrami were manufactured under various climatic conditions. Based on the physical, chemical, microbiological and organoleptic findings of those samples, the "DPx1 sample" produced at 20 °C temperature, 1.5 m/sec weather circulation speed and 65±5 % relative humidity was found to be as the most ideal one. The moisture content and the values of pH and Aw were 41.62 %, 5.45, 0.91 respectively. The level of organoleptic acceptability was quite satisfactory (8,7). Although there was no growth for Coliform microorganisms, a mild increase was observed in the total viable cell count (5.6xl06) and in the numbers of Staphylococci (4.5x103). The same pastrami sample (DPx^) was kept in a vacuum package for the periods of 1,2 and 3 months at room temperature (20 °G). It was deduced that the weight loss decreased to the level of 1. 75 %, the total viable cell count dropped to 2.9xl05, the proliferation of anaerob microorganisms increased to 3 .5xl04, the degree of organoleptic acceptability has not changed significantly (7.9) at the end of 3 months storage period.